2023
DOI: 10.1002/smtd.202201527
|View full text |Cite
|
Sign up to set email alerts
|

Applications of X‐Ray‐Based Characterization in MXene Research

Abstract: X‐rays are a penetrating form of high‐energy electromagnetic radiation with wavelengths ranging from 10 pm to 10 nm. Similar to visible light, X‐rays provide a powerful tool to study the atoms and elemental information of objects. Different characterization methods based on X‐rays are established, such as X‐ray diffraction, small‐ and wide‐angle X‐ray scattering, and X‐ray‐based spectroscopies, to explore the structural and elemental information of varied materials including low‐dimensional nanomaterials. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 134 publications
(330 reference statements)
0
10
0
Order By: Relevance
“…It is well-known that the hydroxyl groups can act as active sites for electrochemical reactions, ultimately leading to an improvement in energy storage. 63 A peak at ∼1550 cm –1 , arising from the vibrational N–H stretching bonds, is present in both the KOH and MgSO 4 electrodes, while being absent in the H 2 SO 4 sample. A plausible explanation for the absence of this peak in the H 2 SO 4 sample could be the presence of excess protons in the electrolyte allowing for the reduction of the N–H bond.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…It is well-known that the hydroxyl groups can act as active sites for electrochemical reactions, ultimately leading to an improvement in energy storage. 63 A peak at ∼1550 cm –1 , arising from the vibrational N–H stretching bonds, is present in both the KOH and MgSO 4 electrodes, while being absent in the H 2 SO 4 sample. A plausible explanation for the absence of this peak in the H 2 SO 4 sample could be the presence of excess protons in the electrolyte allowing for the reduction of the N–H bond.…”
Section: Resultsmentioning
confidence: 93%
“…For all pristine and activated samples, the FTIR analysis revealed the presence of characteristic peaks at ∼3300 and ∼1400 cm –1 , which are assigned to the stretching and bending vibrations of the −OH group, arising from the strong adsorption and coordination of water molecules on the electrode surface. It is well-known that the hydroxyl groups can act as active sites for electrochemical reactions, ultimately leading to an improvement in energy storage . A peak at ∼1550 cm –1 , arising from the vibrational N–H stretching bonds, is present in both the KOH and MgSO 4 electrodes, while being absent in the H 2 SO 4 sample.…”
Section: Resultsmentioning
confidence: 98%
“…The X-ray diffraction (XRD) pattern showed the Al layer had been etched completely owing to the disappearance of the (104) peak that belongs to MAX powders. The (002) peak shifted to a lower angle also ascribed to the removal of Al (Figure c) . The terminal groups (oxygen and fluorine) in MXene were further indicated via energy-dispersive X-ray spectroscopy (EDX) (Figure S3a–e) and X-ray photoelectron spectroscopy (XPS).…”
Section: Resultsmentioning
confidence: 96%
“…The (002) peak shifted to a lower angle also ascribed to the removal of Al (Figure 1c). 20 The terminal groups (oxygen and fluorine) in MXene were further indicated via energy-dispersive X-ray spectroscopy (EDX) (Figure S3a−e) and X-ray photoelectron spectroscopy (XPS). The deconvoluted C 1s, O 1s, and Ti 2p peaks indicated that terminal groups existed on the surface like C−Ti−F x , C−Ti− (OH) x , and C−Ti−O x (Figures S4a−d and S5).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…XPS is less prevalent than other X-ray based techniques due to requirement of synchrotron radiation to achieve the required X-ray brightness. 76 Energy-dispersive X-ray (EDX or EDS) analysis.-This technique is unique from other X-ray based tools as it involves the production of X-rays instead of using it directly. In EDX, the high energy electron beam strikes inner orbit of an atom emitting a charged electron from its shell and creating a positive charged space.…”
Section: X-ray Diffraction (Xrd)-xrd Is An Effective Technique Usedmentioning
confidence: 99%